IMPLICATIONS OF THE QUALITY OF THE PRODUCTION PROCESS ARTISAN CHEESE SERRANO - Pereira, Bianca Pinto; Vieira, Tatiana Regina; Valent, Joice Zagna; Bruzza, Adriano; Wagner, Saionara Araújo; Pinto, Andrea Troller; Schmidt, Verônica (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The Serrano Handmade Cheese (SHC) is a product manufactured on high altitude fields in southernmost Brazil. This region is formed by northeastern Rio Grande do Sul and Santa Catarina Southern Plateau. Originally, this was a overplus good exchanged for another goods by drovers of this region. Currently, the SHC may be responsible for up to 60% of properties income. The SHC is produced with raw milk from cattle ranching within the property. Thus, was performed a descriptive study of literature review aiming to describe the production process of Serrano Handmade Cheese. A look on product quality and food safety theoretical contribuiton was sought also. Considering the technical regulation development to SHC some properties has build appropriate production environments. Those actions are aiming quality and safety of the cheese made. The implementation of Good Agricultural Practice has shown significant quality improvement of the milk used to produce this cheese. The implementation of Good Manufacturing Practice is under study in these producing properties.